lncRNA pair as candidate diagnostic signature for colorectal cancer based on the within-sample relative expression levels - Wang, Ouxi; Shi, Di; Li, Yaqi; Zhou, Xiaoyan; Yan, Haidan; Yao, Qianlan (Frontiers in Oncology, 2022)
Background: Early diagnosis of colorectal cancer could significantly improve the prognosis and reduce mortality. Abnormal expression of lncRNA is associated with initiation and progression of colorectal cancer. It is of great value and clinical significance to explore lncRNAs as candidate diagnostic biomarkers in colorectal cancer. Methods: Based on within-sample relative expression levels of lncRNA pairs, we identified a group of candidate diagnostic biomarkers for colorectal cancer. And validated it in independent datasets produced by different laboratories and different platforms. We also tested it in colorectal cancer tissue samples using quantitative real-time polymerase chain reaction. Results: A biomarker consisting of six lncRNA pairs including 9 lncRNA was identified for the diagnosis of colorectal cancer. For a total of 855 cancer samples and 247 non-cancer samples, both of the sensitivity and specificity could achieve about 90%. For adenoma samples, the accuracy could achieve 73%. Furthermore, the lncRNA pair biomarker showed excellent performance in all clinical stages, even in early stage, the accuracy could achieve 87% and 82% in stage I and II. Meanwhile, the biomarker was also robust to MSI status. More importantly, we measured the biomarker in five colorectal cancer tissue samples using RT-qPCR, and all five samples were correctly identified as cancer samples, indicating that the biomarker might be highly sensitive and robust for different measuring technologies. Conclusion: We identified and validated six lncRNA pairs including 9 lncRNAs as a biomarker for assist in diagnosis of colorectal cancer..